2009
DOI: 10.1590/s0102-76382009000200011
|View full text |Cite
|
Sign up to set email alerts
|

Diabéticos devem ter a artéria torácica interna esqueletizada? Avaliação da perfusão esternal por cintilografia

Abstract: Objective: To assess, by scintillography, the effect of using bilateral internal thoracic arteries (BITAs) -prepared by two different techniques -on the sternal perfusion.Method: 35 patients undergone coronary artery bypass grafting (CABG) were divided into two groups: Group A (18) had both ITA's dissected using skeletonization technique and group B (17) as pedicle preparation. There was no difference in the two groups relating gender, age and demographic characteristics. On the 7 th postoperative day the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…There are very few reports on low early mortality rates and good long-term outcomes with routine use of pedicled bilateral ITA grafts for left-sided myocardial revascularization in insulin-dependent diabetics [21], and it is commonly perceived that pedicled bilateral ITA grafts should not be performed in diabetic patients due to an increased risk of DSWI, leading to mediastinitis, septicemia, and even death [8,9,10,11]. Skeletonization was associated with a high residual sternal blood supply and a reduction in sternal ischemia, subsequently lowering the risk of deep sternal wound complications [12,13,14,15,22,23]. However, few reports have focused on evaluation of the risk of DSWI in diabetic patients undergoing off-pump skeletonized bilateral or single ITA grafting compared to off-pump pedicled ITA grafting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are very few reports on low early mortality rates and good long-term outcomes with routine use of pedicled bilateral ITA grafts for left-sided myocardial revascularization in insulin-dependent diabetics [21], and it is commonly perceived that pedicled bilateral ITA grafts should not be performed in diabetic patients due to an increased risk of DSWI, leading to mediastinitis, septicemia, and even death [8,9,10,11]. Skeletonization was associated with a high residual sternal blood supply and a reduction in sternal ischemia, subsequently lowering the risk of deep sternal wound complications [12,13,14,15,22,23]. However, few reports have focused on evaluation of the risk of DSWI in diabetic patients undergoing off-pump skeletonized bilateral or single ITA grafting compared to off-pump pedicled ITA grafting.…”
Section: Discussionmentioning
confidence: 99%
“…A skeletonized ITA graft compared to a pedicled ITA graft preserves collateral circulation to the sternum and drainage of the internal mammary veins, which reduces the risk of DSWI after CABG surgery. Skeletonized bilateral ITA grafting has been proposed as a possible approach to reduce the incidence of sternal infection while maintaining the benefits of the application of bilateral ITA grafts [12,13,14,15]. However, few reports have focused on evaluation of the merit of skeletonized bilateral or single ITA grafting compared to pedicled ITA grafting in reducing the risk of DSWI in diabetic patients undergoing off-pump CABG (OPCAB) surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Using bone scintigraphy, Korbmacher et al found no perfusion impairment on the LIMA side, although the contralateral side showed an increase in perfusion as a compensatory sign. A similar study in patients with BIMA showed a significant drop in sternal perfusion only in the diabetic subgroup [ 16 ], which could be explained by the missing redistribution of circulation in patients with microangiopathy. All this data points to the idea that the development of SO is a multifactorial process, where contamination, blood supply, and comorbidities play a collective role in the pathogenesis.…”
Section: Discussionmentioning
confidence: 92%